Ewa Mazierska, Popular Viennese Electronic Music, 1990-2015. Issue 2 (21st August 2020) - Bottà, Giacomo
Abstract : Ewa Mazierska,  Popular Viennese Electronic Music, 1990–2015. London and New York: Routledge, 2019. 239 pp. ISBN 978-1-138-71391-8 (hbk).